Loosing thermodynamic stability in amorphous materials - Kokshenev, Valery B. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The primary relaxation dynamics near the glass transformation temperature Tg exhibits universal features in all glass formers, when showing two-level tunneling states (Low Temp. Phys. 35, 282 (2009)). Researchers have long searched for any signature of the underlying “true” ergodic–nonergodic transition emerging at a certain thermodynamic instability temperature Te. Here, the relaxation timescale for glass-forming materials is analyzed within a self-consistent thermodynamic cluster description combined with the cluster percolation concept. Exploring the ergodic hypothesis, its violation is found near a crossover from the Gaussian to non-Gaussian (Poisson) cluster-volume fluctuations, describing the finite-size fractal-cluster distributions. The transformation of the compact-structure “ergodic” clusters into hole-like glassy nanoclusters is attributed to the critical-size thermal fluctuations. The ergodic–nonergodic phase diagram showing Te is predicted in the model-independent form through the glass fragility parameter known for organic and inorganic liquids and amorphous solids. In all cases the ergodic-instability temperature is located below and close to the glass transformation temperature, whereas the distance between the two characteristic temperatures decreases with growing the material fragility.